2022
DOI: 10.5614/j.eng.technol.sci.2022.54.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Microplastics along Mai Khao Coastline, Phuket

Abstract: The distribution of microplastics at Mai Khao beach, Phuket, Thailand was studied. A total of 12 samples from four sample sites with 0.5 m x 0.5 m quadrats were taken at the intertidal zone during March and July, 2020, and sorted into two size classes (>300 µm and 20 to 300 µm). The mean abundance of microplastics at Mai Khao beach ranged from 44.08 to 68.7 items kg-1 d.w. for >300 µm and from 90.6 to 106.1 items kg-1 d.w. for the 20 to 300 µm range. White (44.94%) and blue (23.60%) colors, and fiber sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…The results of this study are consistent with a prior investigation that examined the distribution of MPs in beach sediment on Mai Khao Beach. The previous study revealed a predominance of white (44.94%) and blue (23.60%) MPs, with a prevailing fiber shape (94.5%) [2]. Regarding polymer identification, from the samples subjected to µFTIR analysis, 80% were identified as PET, while the remaining samples consisted of PP, polyamide (PA), and polyether urethane (PU).…”
Section: ) Microplastics In Seawatermentioning
confidence: 96%
See 3 more Smart Citations
“…The results of this study are consistent with a prior investigation that examined the distribution of MPs in beach sediment on Mai Khao Beach. The previous study revealed a predominance of white (44.94%) and blue (23.60%) MPs, with a prevailing fiber shape (94.5%) [2]. Regarding polymer identification, from the samples subjected to µFTIR analysis, 80% were identified as PET, while the remaining samples consisted of PP, polyamide (PA), and polyether urethane (PU).…”
Section: ) Microplastics In Seawatermentioning
confidence: 96%
“…Fibers are a diverse category of synthetic plastic polymers commonly used in the production of clothing, curtains, personal hygiene products, and sanitary items. Another potential source of these synthetic fibers is wastewater from sanitary facilities [1][2].…”
Section: ) Microplastics In Seawatermentioning
confidence: 99%
See 2 more Smart Citations